Sanshools from Zanthoxylum genus and their antioxidant properties in vitro and in vivo - Chen, Zhaojun; Tan, Lulin; Li, Lina; Wang, Hui; Feng, Xin; Liu, Xiong; Rao, Chaolong (Frontiers in Sustainable Food Systems, 2024)
The objective of the present study was to evaluate structure–activity relationships of four sanshools on antioxidant activities. In vitro, hydroxy-α-sanshool (HAS), hydroxy-β-sanshool (HBS), and hydroxy-γ-sanshool (HRS) had stronger antioxidant capacities than hydroxy-γ-sanshool (RS), attributed to the hydroxyl group. Furthermore, HRS had the greatest oxygen radical absorbance capacities (ORAC) and free radical scavenging (DPPH and ABTS) capacities, attributed to more cis-double bonds. Sanshools could effectively decrease the level of oxidative stress in colonic tissue and HCT-116 cells, including increased enzyme activities of catalase (CAT), superoxide dismutase (SOD), and glutathione peroxidase (GSH-Px) and decreased concentrations of malondialdehyde (MDA). After intragastric administration of sanshool, HRS increased the the level of hepatic Total antioxidant capacity (T-AOC) and colon GSH-Px and SOD. Moreover, sanshools significantly increased Nrf2, HO-1 proteins and decreased Keap1 protein. The protective effect of HRS was much higher than HAS, HBS, and RS, apparently due to its amide and hydroxyl groups. The binding energies of Nrf2 with HAS, HBS, HRS, and RS were −5.17, −5.11, −5.75, and −4.16 kcal/mol, respectively. HRS is more easily combine with Nrf2. In summary, sanshools acted as substitutes for natural antioxidants, in which HRS has the greatest antioxidant activity. This study provided a basis for future research on relationships between structure and activity.